If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -20 = 5x + 6 Reorder the terms: -20 + 3x = 5x + 6 Reorder the terms: -20 + 3x = 6 + 5x Solving -20 + 3x = 6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -20 + 3x + -5x = 6 + 5x + -5x Combine like terms: 3x + -5x = -2x -20 + -2x = 6 + 5x + -5x Combine like terms: 5x + -5x = 0 -20 + -2x = 6 + 0 -20 + -2x = 6 Add '20' to each side of the equation. -20 + 20 + -2x = 6 + 20 Combine like terms: -20 + 20 = 0 0 + -2x = 6 + 20 -2x = 6 + 20 Combine like terms: 6 + 20 = 26 -2x = 26 Divide each side by '-2'. x = -13 Simplifying x = -13
| 5z^3-405z=0 | | 11x^2+86x-16=0 | | 2+7z*z= | | 10.3=2t+5.8 | | 6a+2+5a+9=0 | | 0.5x+26=90 | | 2a^2+12=-60 | | -5v-(-76v)-91v=80 | | 2*7z= | | 2x=3y+13 | | X=5x+y | | u=n^2+9n-20 | | 1/4(x-3)=5 | | un=n^2+9n-20 | | 2a+12=-60 | | 19z+(-13z)+(-14z)=88 | | 7z*7z= | | 7x+10=x+120 | | 10-2(m+5)=16 | | 42g-45g+(-93)=-12 | | z*z= | | 13-6x=-38 | | 91v-16v-61v-12v-v=95 | | 16y-24=4y | | 16z-48=4z | | 51=3*3+2*3*h | | X^2+9x-3=5x-7 | | 3x-(x+1)=6m+1 | | 2m+7+3m=-33 | | 6.25y=9 | | 73-x=2x+3 | | 3000=300(10+x) |